Embodied Exclusion: Young Mothers' Experiences of Exclusion from Formal and Informal Sexual Health Education - Greene, Saara (Atlantis, 2008)
Pregnant teenagers and young mothers experience embodied exclusion due to the range of attempts aimed at controlling their sexual behaviour. Embodied exclusion in this context is the result of having the sexual health needs and experiences of pregnant teenagers and young mothers excluded from formal and informal sexual health education.